THE INFLUENCE OF SERVICE QUALITY TOWARDS STUDENT’S SATISFACTION AT ACADEMIC ADMINISTRATION AND STUDENTS AFFAIRS DEPARTMENT (AASA) INSTITUTE OF BUSINESS AND INFORMATICS STIKOM SURABAYA - Sulistiowati (Fakultas Ekonomi Universitas 45 Surabaya, 2018)
Institute of Business and Informatics STIKOM Surabaya (STIKOM Surabaya) is one of the private universities in Surabaya. STIKOM Surabaya has two faculties namely Faculty of Technology and Informatics, and Faculty of Economics and Business. The Faculty of Technology and Informatics has six departments, while the Faculty of Economics and Business has three departments. The department handling academic administration of students from all departments is Academic Administration and Student Affairs Department (AASA). The problem arises is STIKOM Surabaya had a will to evaluate the service quality in AASA based on student’s perceptions which would be used as an input to improve the service quality of AASA. Based on the above problem, then this study was held in order to know the influence of service quality in AASA to student’s satisfaction. The method used in this study was multiple linear regression analysis which measures the influence of service quality in AASA section to the satisfaction of the students of Institute of Business and Informatics STIKOM Surabaya and which factors of the dimensions of service quality that need to be improved. Service quality dimensions include Tangible, Reliability, Responsiveness, Assurance, and Empathy. The results obtained are the dimensions of Reliability and Responsiveness have no effect on student’s satisfaction, while the dimensions of Tangible, Assurance, Empathy of service quality have a positive effect on student’s satisfaction at Institute of Business and Informatics by 63% which has a meaning that any increase of physical display dimensions, assurance, and empathy will increase student’ssatisfaction . Based on the results of the descriptive analysis, it is found that